GENDER-BASED DIFFERENCES IN LEVELS OF WRITING ANXIETY OF UNDERGRADUATE STUDENTS OF ENGLISH STUDY PROGRAM - Anggraini, Hesti Wahyuni (LET: Linguistics, Literature and English Teaching Journal, 2013)
Viewpoints toward writing as the most difficult skill to acquire in EFL setting provide myriad opportunities for students to experience writing anxiety. Also, gender roles in language learning utilize different expectations toward writing anxiety. The study aims at investigating whether there is significant difference in levels of writing anxiety on the basis of gender, 110 undergraduate students, 55 of each, and also what factor(s) are included. For the purposes of finding the significance, it was designed a ready-made 26-item questionnaire named FLCAS in Writing, using Likert-scale. The findings revealed that student?s sex was not significant variable in levels of writing anxiety by the test of significance (2-tailed) of .362 (p>0.05) in independent sample t-test, with insignificant mean difference of 2.145. It reported that male students felt higher levels of writing anxiety than females. The test of factor analysis described factor affecting student?s levels of writing anxiety was mostly on the light of evaluation apprehension, not either stress or product apprehension.